Про північну межу природного поширення Acer tataricum L. (Aceraceae) на Київському Поліссі - Петров, М.Ф. (Український ботанічний журнал, 2011)
Современная естественная северная граница расселения Acer tataricum L. на Киевском Полесье проходит в бассейне р. Уж. Самая северная локальная прогрессирующая популяция вида западнее Днепра расположена в пойме р. Уж возле с. Черевач Киевской обл. На северной границе ареала A. tataricum сохраняется в эдафотопах, периодически обогащаемых минеральными веществами, принесенными поверхностными или почвенными водами. Current natural limits of the range of A. tataricum L. in Kyiv Polissya pass through the watershed basin of the Ouzh River. The northernmost local progressive population of the species to the west of the Dnieper River is located at the floodplain of the Ouzh River near Cherevach village in Kyiv Region. At the northern limits of its range, A. tataricum occurs in edaphotopes enriched with mineral substances transported by the surface or ground waters.